Urea‐based amphiphilic porous organic polymer‐supported palladium as a reusable catalyst for Suzuki–Miyaura coupling and hydroxycarbonylation reactions in water. (20th June 2018) - Lei, Yizhu; Lan, Guosong; Zhu, Dajian; Wang, Renshu; Zhou, Xiao‐Yu; Li, Guangxing
Abstract : The development of environmentally friendly heterogeneous catalysts for organic reactions in water is becoming of growing importance for the development of sustainable processes. In this work, a porous organic polymer‐supported palladium catalyst (Pd@UPOP‐1) was successfully fabricated from 3, 3′‐diaminobenzidine and methylenediphenyl diisocyanate through a facile urea‐forming condensation reaction. The structure and composition of the catalyst were characterized using several physicochemical methods. Pd@UPOP‐1 was found to possess good porous structure and excellent amphiphilicity. Under mild reaction conditions, the catalyst showed excellent catalytic activity and good substrate compatibility for the Suzuki–Miyaura coupling reaction of aryl bromides, as well as the hydroxycarbonylation reaction of aryl iodides. In addition, the catalyst could be used for several consecutive recycles in both cases. Abstract : In this work, a porous organic polymer supported palladium catalyst (Pd@UPOP‐1) was fabricated through a facile urea‐forming condensation reaction. The obtained Pd@UPOP‐1 was found to possess good porous structure and excellent amphiphilicity. With water as the solvent, the catalyst shows excellent catalytic activity and good substrate compatibility for the Suzuki‐Miyaura coupling reaction of aryl bromides, as well as the hydroxycarbonylation reaction of aryl iodides. Moreover, the catalyst can be used up to several consecutive recycles in both cases.